2013
DOI: 10.1088/0143-0807/34/3/679
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dynamics of single-bubble sonoluminescence

Abstract: Sonoluminescence (SL) is the phenomenon in which acoustic energy is (partially) transformed into light. It may occur by means of many or just one bubble of gas inside a liquid medium, giving rise to the terms multi-bubble-and single-bubble sonoluminescence (MBSL and SBSL). In the last years some models have been proposed to explain this phenomenon, but there is still no complete theory for the light emission mechanism (especially in the case of SBSL). In this work, we will not address this more complicated par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…However, given the very short time spans of less than 500 ps over which these extreme pressure amplitudes typically occur, as observed in Figure 14b where the shown time interval corresponds to 877 ps, we conjecture that the thermodynamic system is unable to establish a thermodynamic equilibrium. Studies on the modelling of sonoluminescence, where similarly large pressure values and bubble wall velocities are observed, corroborate the overall applicability of the modelling assumptions used in this study to predict the bubble dynamics (Vignoli et al, 2013;Nazari-Mahroo et al, 2018).…”
Section: Validity and Limitations Of The Modelling Assumptionssupporting
confidence: 78%
“…However, given the very short time spans of less than 500 ps over which these extreme pressure amplitudes typically occur, as observed in Figure 14b where the shown time interval corresponds to 877 ps, we conjecture that the thermodynamic system is unable to establish a thermodynamic equilibrium. Studies on the modelling of sonoluminescence, where similarly large pressure values and bubble wall velocities are observed, corroborate the overall applicability of the modelling assumptions used in this study to predict the bubble dynamics (Vignoli et al, 2013;Nazari-Mahroo et al, 2018).…”
Section: Validity and Limitations Of The Modelling Assumptionssupporting
confidence: 78%
“…It also indicates that the cavitation bubble is less compressed, and the impact velocity released by bubble collapse is significantly weaker when solid particles are added to the base solution. Research has found that the bubble can generate the micro-jet near a rigid interface, where the bubble collapse velocity is greater than the sound velocity of the fluid [35] . Because the bubble collapse velocity of work is one order of magnitude higher than the sound velocity of the MRPF( c ≈ 1481 m/s), the micro-jet near the solid particles can be produced.…”
Section: Resultsmentioning
confidence: 99%
“…The variation mechanism of the bubble surface is the most important part for studying the dynamic characteristic of the bubble in a three-phase flow, so the solving method of the bubble radial will be quite important. To track the time evolution of the bubble radius, the bubble radial differential equation, considering the influence of the bubble surface tension, saturated vapor pressure, constant bubble mass and liquid viscosity [48], can be obtained (Equation (10)) based on the RP equation [10,14].…”
Section: Bubble Radial Differential Equationsmentioning
confidence: 99%
“…The results indicated that the ultrasonic wave with the frequency of 3.24 Mhz can make the bubble with a maximum radius of 150 µm produce 80-130 m/s micro-jet. Vignoli [14] showed that a high-speed micro-jet will appear only when the bubble collapse speed is higher than the propagation sound velocity in liquid. Li J [15] conducted the VOF to simulate the cavitation collapsing near the wall and to calculate the influence of the distance between the cavitation collapse and the wall on the jet strength.…”
Section: Introductionmentioning
confidence: 99%